CALLOGENESIS IN LEAF SEGMENTS OF Mammea americana L. - RODRIGUES FERREIRA, MARIA DAS GRAÇAS; ALVES DOS SANTOS, MAURÍCIO REGINALDO; BARROS ROCHA, RODRIGO (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2016)
Apricot tree is a native species from West Indias belonging to the Clusiaceae family. The fruit is consumed in natura as juices, candies, liquors, etc. The in vitro propagation is presented as an alternative technique for the species propagation, contributing for the production of plants with uniform genetic characteristics, identical to the mother plant, diseases free, with the production of many of plants in a small space, independent of the time of the year. The objective of the present work was to establish a protocol for callogenesis induction in leaf segments of apricot tree. Leaf segments were used as explants, which were inoculated in MS, WPM and Knudson media, supplemented with 2,4-D (0.0; 2.0 and 4.0 mg L-1) and BAP (0.0; 2.0 and 4.0 mg L-1), sucrose (0.3%), agar (0.8%) and pH adjusted to 5.8. The Knudson medium pH was adjusted to 4.8. The calli formation was more efficient using the MS medium containing 2.0 mg L-1 2,4-D + 2.0 mg L-1 BAP.